Ekstrakurikuler Drumband sebagai Sarana Pengembangan Motorik dan Kognitif Anak Usia Dini di TK Aisyiyah Bustanul Athfal 50 Surabaya - Choirunnisya Choirunnisya; Hanesya Izzah Salsabillah; Siti Aisyah Haramainy; Ratna Pangastuti (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to analyze in depth the role of drumband extracurricular activities in developing motor and cognitive abilities of early childhood at Aisyiyah Bustanul Athfal 50 Kindergarten, Surabaya. This study uses a qualitative approach with data collection methods through direct observation, in-depth interviews, and the distribution of questionnaires involving teachers, parents, and students as research subjects. The results show that drumband activities provide a positive contribution to the development of gross and fine motor skills of children, especially through rhythmic movement exercises, hand-eye coordination, and body control when playing musical instruments. In addition to motor aspects, drumband activities also play a role in improving children's cognitive abilities, such as concentration, memory, the ability to follow instructions, and understanding musical patterns and rhythms. Children's active participation in drumband activities also helps shape discipline, the ability to work together in groups, and increases children's self-confidence. Thus, drumband extracurricular activities can be used as an effective and enjoyable learning medium to support the motor and cognitive development of early childhood holistically and sustainably.